Fixing the taxonomic identity of Oestrelata feae Salvadori, 1899, through designation of a lectotype, with comments on the type series of Pterodroma mollis deserta Mathews, 1934 (Aves: Procellariiformes: Procellariidae) - Kirwan, Guy M.; Borgo, Enrico; Doria, Giuliano; Field, Daniel J.; Petts, Rachel; Grouw, Hein Van (Zootaxa, 2026)
Taxonomic interest in the Pterodroma petrels of the north-eastern Atlantic Islands has mushroomed in recent decades; all three taxa breeding in this region are now frequently treated as separate species—Fea’s (or Cape Verde) Petrel P. feae in the Cape Verdes, Desertas Petrel P. deserta in the Desertas group, and Zino’s Petrel P. madeira on the main island of Madeira. Oestrelata feae Salvadori, 1899, was described on the basis of five specimens mentioned in the original description, of which two were collected on the island of São Nicolau, in the Cape Verde archipelago, and three from small islands in the Madeira group. Thirty-five years later, Mathews described Pterodroma mollis deserta from an unstated number of specimens also collected in the Desertas group, in the southern part of the Madeiran archipelago. Until the late 1990s, the fact that there were more than just two syntypes of Oestrelata feae was not widely appreciated, and the import of the type series being mixed was under-appreciated due to P. deserta then being generally considered a synonym of feae, rather than a valid taxon. To fix the identity of Oestrelata feae on the universally understood taxonomic concept associated with the name, we designate a lectotype from the one of the two São Nicolau specimens. We also clarify that the type series associated with Mathews’ nomen deserta comprises four syntypes, rather than a single specimen (holotype).